Model of sustainable land management (study at Bukit Sepuluh Ribu area of Bungursari Sub-District, Tasikmalaya City, West Java) - Dadan Ramdhani; Suyud Warno Utomo; Hasrol Thayib; Yuki Wardhana (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2019)
This study is associated with the increased pressure on hill resources due to land conversion that causes environmental degradation and leads to environmental unsustainability. The evenly spread hill known as Bukit Sepuluh Ribu, is a source of community life. The hill formed by the eruption of a volcano, has a land cover, namely close to forest vegetation. The study location is in Bukit Sepuluh Ribu area that has ecological, hydrological, geological and aesthetic environmental function. The concept of community empowerment through Agro-ecosystem can be a solution, thus the utilization of the hill is economically profitable and environmentally sustainable. There are land use unsuitability referring to the existing spatial plan (682.9 Ha), namely high densely settlement area (264.67 Ha), other agriculture (359.21 Ha) and mining areas (58.51 Ha), Through the concept of appropriate community empowerment in accordance with the rules and typology of hill areas can provide the potential benefits of ecosystems and produce products of economic value without damaging them. The concept of empowerment through dryland agro-ecosystem by combining forest-based agriculture activities is one of the solutions to the problem of land management.